Analysis of Cross-Sector Collaboration in the Implementation of Burial Ground Utilization Authorization (IPTM) in DKI Jakarta Province - Erdy Saparudi; Eko Ramadhan (Monas: Jurnal Inovasi Aparatur, 2026)
The Provincial Government of DKI Jakarta bears the responsibility of providing public services to its citizens throughout all stages of life, from birth to death. Within the scope of death‑related services, families of the deceased must obtain four essential documents: the Certificate of Cause of Death (SKPK) issued by a Community Health Center or Hospital; the Death Certificate issued by the Population and Civil Registration Office; the Burial Permit Cover Letter issued by the Public Cemetery (TPU) Administration under the Department of Parks and Urban Forests; and the Burial Ground Utilization Authorization (IPTM) issued by the Investment and One‑Stop Integrated Services Office. Using a qualitative approach, including document reviews and analysis of official reports, this study evaluates the extent of cross-sector collaboration in the provision of death-related services. The findings reveal an absence of effective interagency collaboration, resulting in inefficiencies and reduced service effectiveness. The interdependence among required documents is not supported by integrated operational procedures, leading to slow service delivery and added burdens for grieving families. As a contribution, this study highlights the urgent need to accelerate the development of a one‑stop service system for death-related administrative processes to reduce bureaucratic redundancy and promote a more humane and responsive model of public service governance.